Eruptive lobular hemangioma (pyogenic granuloma) in children. Analysis of 104 cases. - Garofalo, L.; Milano, A. (European Journal of Pediatric Dermatology, 2014)
The distribution by sex and age of 104 cases of eruptive lobular hemangioma (ELH) observed in the last eight years in children aged 0 to 13 years was analyzed. Females (62) outnumbered males (42) by 1.5 to 1. The average age in this population was 5.5 years, but half of the cases was included in the first 3 years of life and 26% between 10-13 years. The head was the most common site, the lower limbs the rarest. The average diameter of the lesions at the time of the removal was 5 mm (1-12). We did not find a relationship between trauma and ELH, except in a case of satellitosis after removal of an angioma; exceptionally a case of ELH developed under a molluscum contagiosum.